PER-OPERATIVE FINDINGS OF BLOCKED VENTRICULOPERITONEAL SHUNT: A STUDY OF 72 CASES - Khan, Muhammad Usman; Ali, Mumtaz; Hussain, Syed Javed; Ullah, Nadeem; Khanzada, Khalid; Ayub, Shahid (Journal of Ayub Medical College Abbottabad, 2009)
Background: Most patients with hydrocephalus are treated with ventriculo-peritoneal (VP) shunt placement; however, malfunction is common and is usually caused by mechanical failure. The aim of this study was to evaluate the per-operative findings accompanying presumed VP shunt malfunction. Methods: This is a descriptive study of 72 patients operated for shunt malfunction in the Department of Neurosurgery, Postgraduate Medical Institute, Lady Reading Hospital, Peshawar from January to December 2008. Presenting symptoms and signs, clinical shunt function, operative findings and outcome were recorded. Results: Common presenting features were vomiting, irritability and general toxic look of patients. Male to female ratio was 3:1. Upper end block was observed in 39 patients while lower end and reservoir block was noted in 13 and 2 patients respectively. Choroids plexus was found in 29.2% of cases with upper end block, shunt revision was performed in most of cases (80.6%). Conclusion: The importance of clinical features cannot be overlooked in a patient with shunt malfunction. Upper end block due to choroids plexus is common operative finding. Keywords: VP shunt, shunt malfunction, choroid plexus